Sistem Monitoring Pasang Surut Air Laut Berbasis Web Menggunakan Fuzzy Logic Pada Kuala Langsa - Muhammad Khalid; Rizalul Akram; Khairul Muttaqin (Journal of Information and Technology, 2022)
Abstract - Tides are a phenomenon of periodic and periodic ups and downs of sea level movements. The tidal period is the time between the crest of a wave to the crest of the next wave, the time of the tidal period varies from 12 hours 25 minutes to 24 hours 50 minutes. Information about tides is very useful for activities related to the marine world. In the area of ​​​​Kuala Langsa, tides often occur, fishermen and anglers in Kuala Langsa only rely on the poles of residents' houses to determine the time of the tide. The system is made useful so that fishermen and anglers can find out the time and state of the tides using smartphones, by creating a “Sea Tidal Monitoring System using Ultrasonic Sensors and nodeMCU which can provide results of monitoring the time and tidal status in Kuala Langsa and will displayed on a Web page”. Ultrasonic sensors can detect well and can provide tidal data to be displayed on a web page and can be accessed using smartphones and other devices during the testing period in Kuala Langsa village, Langsa City with 62.5% success being tested.